Hubungan Pengetahuan tentang Vaksin Covid-19 dengan Tingkat Kecemasan pada Kelompok Lansia di Desa Tanjung Aur II - Susilawati, Susilawati; Sari, Priski Leka; Yanti, Lussyefrida (Universitas Malahayati, 2023)
ABSTRACT Covid-19 is a type of infectious disease caused by sever acute respiratory syndrome coronavirus 2 (SARS-Cov-2). Currently, a Covid-19 vaccine has been found that can reduce the rate of its spread. This study aims to find a relationship between knowledge about the COVID-19 vaccine and the level of anxiety in the elderly group in Tanjung Aur II Village. The method used is an analytic observational design using a cross sectional approach, which aims to find out the actual relationship between knowledge about the COVID-19 vaccine and the level of anxiety in the elderly group in Tanjung aur II Village. The sampling technique in this study was using purposive sampling. The instrument used is a questionnaire sheet. Data analysis was univariate and bivariate using the chi square test with the Confidence level (0,05). The results of the study with the Chi-Square test (0,008) < 0.05, then Ha is accepted, H0 rejected. The meaning that there is a relationship between knowledge about the covid-19 vaccine and the level of anxiety in the elderly group in tanjung Aur II Village. Keywords: COVID_19, Elderly, Vaccine ABSTRAK COVD-19 yaitu jenis penyakit menular yang disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2). Saat ini telah ditemukan vaksin Covid-19 yang dapat menekan laju penyebarannya. Penelitian ini bertujuan untuk menemukan adanya hubungan antara pengetahuan tentang vaksin COVID-19 dengan tingkat kecemasan pada kelompok lansia di Desa Tanjung Aur II. Metode yang digunakan adalah desain observasional analitik menggunakan pendekatan cross sectional, yang bertujuan untuk mengetahui secara actual mengenai hubungan pengetahuan tentang vaksin Covid-19 dengan tingakt kecemasan pada kelompok lansia di DESa Tanjung Aur II. Teknik pengambilan sampel pada penelitian ini adalah menggunakan Purposive Sampling. Instrument yang digunakan adalah lebar angket kuesioner. Analisa data secara univariat dan bivariat dengan menggunakan uji Chi-kuadrat. Hasil penelitian dengan uji Chi-kuadrat α (0,028) < 0,05, maka Ha diterima, H0 ditolak. Ada hubungan antara pengetahuan tentang vaksin Covid-19 dengan tingkat kecemasan pada kelompok lansia di Desa Tanjung Aur II Kata Kunci: Covid-19, Lansia, Vaksin